The effect of financial technology–digital payment systems on business profitability of MSMEs in Ternate City - Ramdani, Aisah; Saerang, David P. E.; Budiarso, Novi Swandari (Yayasan Widyantara Nawasena Raharja, 2026)
The rapid development of financial technology has transformed business transaction systems, particularly through the adoption of digital payment platforms. For micro, small, and medium enterprises (MSMEs), digital payment systems are expected to enhance operational efficiency, expand market access, and ultimately improve business profitability. However, empirical evidence regarding the effectiveness of digital payment adoption in improving MSME performance, especially in geographically constrained regions, remains limited. This study aims to examine the effect of digital payment systems on the profitability of culinary MSMEs in Ternate City, Indonesia. A quantitative research approach was employed using primary data collected through questionnaires from 97 MSME owners selected using purposive sampling. Data were analyzed using simple linear regression with the assistance of SPSS version 27. The results indicate that digital payment systems have a positive and statistically significant effect on MSME profits, with a significance value of 0.009 (p < 0.05). Nevertheless, the coefficient of determination (R² = 0.069) suggests that digital payment adoption explains only a small proportion of profit variation, indicating that other factors also contribute to MSME financial performance. These findings support the perspectives of behavioral accounting and transaction cost theory, which highlight the role of technology adoption in improving transaction efficiency and business outcomes. The study contributes to the growing literature on fintech adoption in MSMEs and provides empirical evidence from an island-based regional economy.